Physical characterization of oleic acid polyol based polyurethane coatings / Thamil Selvi Velayutham - Thamil Selvi, Velayutham (2009)
The research studies focus on physical characterization of oleic acid polyol based polyurethane (PUR) coatings. Basically, polyurethanes are derived from the reactions between polyols and isocyanates. The most common polyols used in PUR production are made from petroleum derivatives. In this research, a new technology has been developed which results in producing PUR coatings based on polyols synthesized from oleic acid. Three different polyols, with various oleic acid contents were used in the preparation of polyurethane (PUR) coatings. The polyols were designated as Alk28, Alk40 and Alk65, in which 28, 40 and 65 represents the oleic acid percentage of the polyols formulation. These polyols were reacted with aromatic isocyanate (toluene 2, 4- diisocyanate, TDI) to form PUR coatings. Properties such as acid number and hydroxyl value of the polyols have been determined. The polyols were characterized by Infrared (IR) spectroscopic. By varying the oleic acid content in the polyols, the amount of flexible side chains incorporated in the polymer was varied. On the other hand, the NCO/OH ratios of the PURs samples were varied to see the cross-linking effects as the ratios increased. The characterization of PURs coating were carried out by IR spectroscopy, DSC analysis, TGA analysis and XRD analysis. Physico-chemical properties such as drying time, pencil hardness, adhesion properties, solvent resistance and corrosion/chemical resistant determination were reported. The PUR made from the lowest oleic acid content exhibited the best overall physical properties followed by the medium and the highest oleic acid content. The properties were enhanced as the NCO/OH ratio increased. A part of the research was concentrated on electrical properties of the materials. Two types of conductivity measurement were performed which involved alternative current, ac and direct current, dc. The purpose of performing the ac and dc conductivity measurements for the PURs was to investigate the alternating current response as a function of the frequency to the applied field in order to study the dielectric behaviour of the material. The nature of conduction mechanism involved in the PUR was also determined. Mechanical and creep properties of the samples were also determined in the studies. The analysis revealed that the PURs made with polyols of the lowest oleic acid content have the best mechanical and creep properties due to introduction of higher degree of cross-linking.